LEMBAGA PENDIDIKAN YANG BERJIWA NASIONAL - Sarmila; Mulia Suryani; Tri Andini Putri; Revienna Aulia Putri; Rina; Ine Febrianti (Jurnal Binagogik, 2025)
Education holds a strategic role in shaping national character and instilling values of nationalism, particularly for the younger generation as the future leaders of the nation. The history of education in Indonesia records the significant contribution of several national-spirited educational institutions, both before and after independence. Institutions such as Taman Siswa, Muhammadiyah, INS Kayu Tanam, and Diniyah Puteri Padang Panjang not only served as centers for disseminating knowledge but also as platforms for intellectual and nationalist movements. This study aims to explore the historical contributions and contemporary relevance of the national values upheld by these institutions within Indonesia’s current education system. The research employs a library research method using content analysis techniques on various literature sources and previous studies. The findings reveal that the spirit of nationalism once promoted through education has gradually weakened in the modern era, largely due to globalization and the rapid advancement of technology. The Merdeka Curriculum has yet to fully integrate nationalist values in a structured and systematic manner. Therefore, reinforcing national values through character education rooted in the legacy of national education institutions is deemed essential. This study concludes that revitalizing nationalism within the national curriculum is crucial to preserving Indonesia’s identity amidst the challenges of globalization.